A Systematic Study of Structure and E−H Bond Activation Chemistry by Sterically Encumbered Germylene Complexes. Issue 33 (6th July 2016) - Usher, Matthew; Protchenko, Andrey V.; Rit, Arnab; Campos, Jesús; Kolychev, Eugene L.; Tirfoin, Rémi; Aldridge, Simon
Abstract: A series of new germylene compounds has been synthesized offering systematic variation in the σ‐ and π‐capabilities of the α‐substituent and differing levels of reactivity towards E−H bond activation (E=H, B, C, N, Si, Ge). Chloride metathesis utilizing [(terphenyl)GeCl] proves to be an effective synthetic route to complexes of the type [(terphenyl)Ge(ER n )] (1 –6 : ER n =NHDipp, CH(SiMe3 )2, P(SiMe3 )2, Si(SiMe3 )3 or B(NDippCH)2 ; terphenyl=C6 H3 Mes2 ‐2, 6=Ar Mes or C6 H3 Dipp2 ‐2, 6=Ar Dipp ; Dipp=C6 H3 i Pr2 ‐2, 6, Mes=C6 H2 Me3 ‐2, 4, 6), while the related complex [(Me3 Si)2 NGeB(NDippCH)2 ] (8 ) can be accessed by an amide/boryl exchange route. Metrical parameters have been probed by X‐ray crystallography, and are consistent with widening angles at the metal centre as more bulky and/or more electropositive substituents are employed. Thus, the widest germylene units ( θ >110°) are found to be associated with strongly σ‐donating boryl or silyl ancillary donors. HOMO–LUMO gaps for the new germylene complexes have been appraised by DFT calculations. The aryl(boryl)‐germylene system [Ar Mes GeB(NDippCH)2 ] (6 ‐Mes), which features a wide C‐Ge‐B angle (110.4(1)°) and (albeit relatively weak) ancillary π‐acceptor capabilities, has the smallest HOMO–LUMO gap (119 kJ mol −1 ). These features result in 6 ‐Mes being remarkably reactive, undergoing facile intramolecular C−H activation involving one of the mesityl ortho ‐methyl groups. The related aryl(silyl)‐germylene system, [Ar Mes GeSi(SiMe3 )3 ] (5 ‐Mes) has a marginally wider HOMO–LUMO gap (134 kJ mol −1 ), rendering it less labile towards decomposition, yet reactive enough to oxidatively cleave H2 and NH3 to give the corresponding dihydride and (amido)hydride. Mixed aryl/alkyl, aryl/amido and aryl/phosphido complexes are unreactive, but amido/boryl complex 8 is competent for the activation of E−H bonds (E=H, B, Si) to give hydrido, boryl and silyl products. The results of these reactivity studies imply that the use of the very strongly σ‐donating boryl or silyl substituents is an effective strategy for rendering metallylene complexes competent for E−H bond activation. Abstract : A germy business : A systematic study of the effects of the α‐substituents on the geometric/electronic structure and reactivity of acyclic germylene complexes reveals that wide R(X)Ge angles, narrow HOMO–LUMO gaps and high reactivity towards E−H activation are associated with systems bearing boryl or silyl groups at X.